Iowa RBA, February 5-7, 1996 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for February 5-7, 1996. Highlights of the update include sightings of a Hoary Redpoll, Snowy Owl, Varied Thrush and a Great Gray Owl. Epson - sheet feed/flatbed